Site-specific irrigation : improvement of application map and a dynamic steering of modified centre pivot irrigation system - Hezarjaribi, Aboutaleb; Justus Liebig University Giessen (My University, 2008)
The need for irrigation may differ between zones of a particular field due to the spatial variation of soil properties or the cropping of different plants on the same field. While moving irrigation systems apply water at constant rates, some areas of the field may receive too much water and others not enough. Therefore the key objectives of the present study were a) Delineation of irrigation management zones (IMZs) using sensor-based soil electrical conductivity (ECa) measurement with the aid of EM38 and VERIS 3100, b) Developing and evaluating a precision mobile drip irrigation (PMDI) and c) Evaluating wireless EnviroSCAN sensors and AMBAV-models to measure the soil moisture content. Soil electrical conductivity in 25 °C were collected using EM38 and VERIS 3100 at field capacity on a 16.6 ha non-saline field in the Federal Agricultural Research Centre, Braunschweig, Germany. 29 calibration points taken at a depth of 60 cm depth were located using differential GPS based on the soil electrical conductivity spatial variability pattern to determine the best sensor-based method to monitor total available water content. The second span of the centre pivot irrigation machine was modified to precision mobile drip irrigation and controlled for variable-rate water application. A better value of R2 between total available water content and the VERIS 3100 readings was found. The R2 value from VERIS 3100-sh data for TAWC estimation was maximally (0.77) and matched the TAWC data quite well, whereas R2 values to EM38-h and EM38-v data were low. Six irrigation management zones were identified based on fuzzy k-means unsupervised classification as an optimum number of irrigation management zones. It was concluded that under conventional uniform irrigation, irrigation management zones 1 and 2 were over-irrigated, whereas irrigation management zones 4, 5 and 6 were under-irrigated. The developed concept of pulse irrigation was a feasible and a viable technique. Water application was directly proportional to the fraction of time the valve was opened. AMBAV model as a cheap and reliable alternative instead of the expensive and imprecise EnviroSCAN sensor was capable of simulating soil moisture in the root zone of grass crops. Precision mobile drip irrigation was able to save about 70 % of energy and about 25 % of water in comparison with centre pivot irrigation system. Although PMDI causes more annual fixed expenses than CP irrigation, it has less total irrigation cost per hectare and year than centre pivot and drip irrigation.

Die Bewässerung zwischen den Bereichen eines Feldes kann auf Grund der Variabilität der Bodeneigenschaften oder dem Anbau von verschiedenen Pflanzen auf demselben Feld variieren. Die Bewässerungssysteme verteilen das Wasser bis heute gleichmäßig, so dass die Flächen teilweise überbewässert oder unterbewässert sind. Folglich sind die Schlüsselziele dieser Arbeit: a) die Abgrenzung von Beregnungsmanagementzonen unter Nutzung von sensorbasierten Messungen der elektrischen Leitfähigkeit (ECa) des Bodens mit EM38 und VERIS 3100, b) die Entwicklung und Evaluierung einer teilflächenspezifischen mobilen Tropfbewässerung und c) Auswertung des drahtlosen EnviroSCAN Sensors und des AMBAV-Modells, zur Bestimmung der Bodenfeuchte. Elektrischen Leitfähigkeit bei 25 °C wurden unter Verwendung von EM38 und VERIS 3100 Geräten bei Feldkapazität auf einem 16.6 ha großen Feldstück der Bundesforschungsanstalt für Landwirtschaft, Braunschweig, Deutschland, gemessen. 29 Kalibrierungspunkten wurden mit Hilfe von differentielle GPS lokalisiert, um die beste sensorbasierte Methode zur Abgrenzung der Beregnungsmanagementzonen zu bestimmen. Bodenproben wurden in 0-60 cm Tiefe entnommen. Der 2. Bogen der Kreisberegnungsanlage wurde für die teilflächenspezifischen mobilen Tropfbewässerung und einer kontrollierten Wassermenge umgerüstet. Ein gutes Bestimmtheitsmaß wurde zwischen nutzbare Feldkapazität und den VERIS 3100 Werten gefunden. Eine Kalibrierungsgleichung zur Abschätzung der nutzbare Feldkapazität VERIS 3100-sh zeigte eine hohe Ähnlichkeit zu den nutzbare Feldkapazität Daten auf und hatte das höchste Bestimmtheitsmaß (R2 = 0.77). Die Bestimmtheitsmaße zu EM38-v und EM38-h Daten waren niedrig. Sechs Beregnungsmanagementzonen wurden als optimale Anzahl an Beregnungsmanagementzonen auf dem Versuchsfeld, basierend auf den fuzzy k-Mittelwerten der zufälligen Einteilung, erkannt. Es wurde gefolgert, dass unter konventioneller Beregnung Beregnungsmanagementzonen 1 und 2 überbewässert und Beregnungsmanagementzonen 4, 5, und 6 unterbewässert wurden. Das entwickelte Konzept der Pulsbewässerung hat sich als eine zuverlässige Technik bewährt. Die Wasserapplikationsmenge war direkt proportional zur Öffnungsdauer des Ventils. Das AMBAV-Modell hat sich als eine Alternative zum kostenintensiven EnviroSCAN erwiesen, das in der Lage ist, die Bodenfeuchtigkeit in der Wurzelzone der Graspflanzen als eine preiswerte und verlässliche Methode zu simulieren. Der Energybedarf kann um 70 % und der Wasserbedarf kann um 25 % gegenüber Kreisberegnungsanlage gesenkt werden. Obwohl teilflächenspezifischen mobilen Tropfbewässerung teurer ist als Kreisberegnungsanlage Bewässerung, verursacht sie weniger Wasser- und Energiekosten als die Kreisberegnungsanlage.
Teilflächenspezifische Beregnung : Entwicklung von Beregnungsapplikationskarten und einer dynamischen Steuerung für Kreisberegnungsmaschinen
Keywords: ddc:630